Переcелення польського населення з території Волинської області в Польщу в 1944−1946 рр. - Пронь, Тетяна; Pron, T. (Волинський національний університет імені Лесі Українки, 2012)
У статті розглянуто процес масового організованого переселення польського населення з території Волинської області в Польщу в 1944−1946 рр., здійснений змішаною польсько-українською комісією згідно з укладеною 9 вересня 1944 р. угодою між урядом УРСР і Польським комітетом національного визволення. This article discusses the process of mass organized resettlement of the Polish population from the territory of Volyn region of Poland in 1944−1946 years. It was held a mixed Polish Ukrainian Commission in accordance with the laid September 9, 1944 Agreement between the Government of the USSR and the Polish Committee of National Liberation.
Resettlement of the Polish Population from the Territory of Volyn Region of Poland in 1944−1946 Years
Keywords: переселення; евакуація; депортація; переміщення населення; західноукраїнські землі; Волинська область; Західна Волинь; «східні креси»; relocation; evacuation; deportation; population transfer; Western Ukraine; Volyn region; the Western Volyn; «Eastern peasants being»